2004
DOI: 10.1021/jf040203x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cigarette Tobacco by Direct Electrospray Ionization−Ion Trap Mass Spectrometry (ESI-ITMS) Analysis of the Aqueous ExtractA Novel and Simple Approach

Abstract: In support of the efforts to combat smuggling, as well as illegal sale and distribution of cigarettes, an analytical approach for the characterization of tobacco has been proposed and evaluated. It involves aqueous extraction of the filler tobaccos followed by direct analysis of the extracts by electrospray ionization-ion trap mass spectrometry (ESI-ITMS) in the negative mode. Typically, the deprotonated ions, [M - H](-), of organic acids (malic, citric, caffeic, quinic acid) and polyphenols (chlorogenic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 3 publications
1
17
0
1
Order By: Relevance
“…Analysis of quinic acid has also been reported in different materials, such as in tea (9), but quantitative information regarding the level of this compound in tobacco is scarce (4,10). A method for the joint analysis of myo-inositol and quinic acid in tobacco is described in this present study.…”
mentioning
confidence: 86%
“…Analysis of quinic acid has also been reported in different materials, such as in tea (9), but quantitative information regarding the level of this compound in tobacco is scarce (4,10). A method for the joint analysis of myo-inositol and quinic acid in tobacco is described in this present study.…”
mentioning
confidence: 86%
“…Notably, citric acid gave a predominant product ion at m/z 111 while quinic acid has specific product ions at m/z 85, 93 and 127, as reported previously. 66 By tandem MS it was confirmed that the peaks at m/z 191 were from quinic acid in apple while such peak came from citric acid in strawberry. Fig.…”
Section: Maldi and Galdi Ms Of Standard Mixtures Of Fatty Acids Flavmentioning
confidence: 96%
“…62 Spraying a matrix solution electrically or pneumatically, immersing the sample in matrix solution, and dispensing matrix solution by a piezoelectric microdispenser were suggested for generating homogeneous sample surface with matrixes. [63][64][65] Recently, Aerni and coworkers used acoustic droplet ejection 66 The laser source in this mass spectrometer is a fiber-optic guided N 2 laser (337 nm, and maximum 280 µJ/pulse before entering the optical fiber cable). The measured laser spot size is about 100 µm in diameter on the sample plate surface.…”
Section: Introductionmentioning
confidence: 99%
“…Useful sample classification methods without previous chromatographic separation have been described by using mass spectrometry (MS). For this purpose, the samples have been directly infused into the mass spectrometer using an electrospray ionization (ESI)19–23 or an atmospheric‐pressure photoionization (APPI)24 ion source. Amino acid profiles obtained by protein hydrolysis have been used as fingerprints to classify protein‐binding media used in works of art according to their biological sources,22, 25 vegetable oils in accordance to their botanical origin,26 rice cultivars,27 and tea varieties,28 as well as to authenticate high quality beer 29.…”
mentioning
confidence: 99%